Systematic Review: Bridging the Gap in RPN‐to‐RN Transitions. Issue 4 (15th June 2015) - Suva, Grace; Sager, Shelley; Mina, Elaine Santa; Sinclair, Nancy; Lloyd, Monique; Bajnok, Irmajean; Xiao, Sarah
Abstract Purpose To review the evidence examining the influences of successful education and professional role transition for registered practical nurses (RPNs) pursuing a baccalaureate degree in nursing (BScN) and registered nurse (RN) licensure through RPN‐to‐RN bridging programs. Design Systematic review of papers published between 1995 and 2014 that evaluated students' education and professional role transitions from RPN to RN. Methods Thirty‐nine papers were selected that observed or studied the change or transition in designation from RPN to RN, or its equivalent, through bridging programs and analyzed thematically according to Meleis, Sawyer, Im, Hilfinger Messias, and Schumacher's transition model. Findings Personal, community, and social conditions related to preparation for entry, program enrolment, and postgraduate clinical integration influence successful education and professional role transitions for RPN‐to‐RN bridging students. Conclusions Providing key transition supports may enhance the potential for successful student transition into and throughout a bridging program, but further research is necessary to enhance this understanding and to recommend best practices for optimizing students' success. Clinical Relevance The evidence from this review identifies facilitators and barriers to successful education and professional role transition for RPN‐to‐RN bridging students, and identifies important considerations for future research.